Quality management and a balanced scorecard as supporting frameworks for a new management model and organizational change - Pimentel, L.; Major, M. (Total Quality Management and Business Excellence, 2014)
The purpose of this paper is to examine how the implementation of quality management and total quality management (TQM) particularly contribute to organisational change, and to analyse the impact of integration of TQM and of a balanced scorecard (BSC) into a new management model and into the effectiveness of an organisation. The paper adopts a descriptive longitudinal case study, and deals with the implementation of innovative management frameworks in a Portuguese government agency. The study was built on quality management/business excellence and on performance measurement systems (PMS)/BSC literature. The main findings of the paper show that a new management model of the organization, based on a quality management programme (particularly TQM), and on a performance measurement programme (basically a BSC) proved to be efficient. Moreover, evidence shows that TQM contributed to organisational change and to increase of financial performance. The paper contributes to the literature on quality management by highlighting the role of quality management and TQM as important tools to help organisations to change and to improve efficiency and financial performance. It also contributes to show that organisations can integrate successfully quality management and PMS/BSC, which is a topic slightly investigated within scientific literature. Furthermore it covers a government agency where few practical situations have been studied. These implications are important for academics and for practitioners.